PENYULUHAN MENGENAI ASPEK HUKUM HAK KEKAYAAN INTELEKTUAL BAGI SISWA SISWI SMKN 1 BANGIL PASURUAN - Budi Hermono; Eny Sulistyowati; Muh. Ali Masnun; Irfa Ronaboyd; Dita Perwitasari; Arinto Nugroho (Universitas Majalengka, 2021)
The minds that exist in humans, if used optimally, will certainly produce various kinds of intellectual works that can have moral rightsand economic rights. Educational institutions as a place for every human being who exploits their intellect have quite a lot of intellectual property from the results of their teaching and learning process. Vocational Schools are a form of formal education units that provide vocational education at the secondary education level as a continuation of SMP / MTs. Intellectual property protection for the works of vocational high school students is a very important step for the Indonesian nation in entering the free market era where the more advanced a country is, the more dependent it is on its intellectual capital which has business value so that it brings in investors to encourage willingness in research. PKM results show: (1) students have relatively understood the material related to intellectual property rights based on the comparison ofscores pre and posttest that have increased (2) Students have legal awareness to protect the results of intellectual property they produce. (3) There is a desire on the part of the school, to hold outreach with a larger number of students so that the level of awareness and understanding will increase and be broader.